2020
DOI: 10.1177/2041731420949332
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of excessive scar formation using nanofibrous meshes made of biodegradable elastomer poly(3-hydroxybutyrate-co-3-hydroxyvalerate)

Abstract: To reduce excessive scarring in wound healing, electrospun nanofibrous meshes, composed of haloarchaea-produced biodegradable elastomer poly(3-hydroxybutyrate- co-3-hydroxyvalerate) (PHBV), are fabricated for use as a wound dressing. Three PHBV polymers with different 3HV content are used to prepare either solution-cast films or electrospun nanofibrous meshes. As 3HV content increases, the crystallinity decreases and the scaffolds become more elastic. The nanofibrous meshes exhibit greater elasticity and elong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“… 40 To reduce excessive scarring in wound healing, some researchers used polymer meshes as a wound dressing to treat wound. 41 In this study, we added a plastic clip between the 3D-printed PLCL scaffold with/without MFUS and the wound edge skin to block the upper layer skin cell migration. It is well known that skin wounds generally heal by scarring, a fibrotic process mediated by the Engrailed-1 (En1) fibroblast lineage.…”
Section: Discussionmentioning
confidence: 99%
“… 40 To reduce excessive scarring in wound healing, some researchers used polymer meshes as a wound dressing to treat wound. 41 In this study, we added a plastic clip between the 3D-printed PLCL scaffold with/without MFUS and the wound edge skin to block the upper layer skin cell migration. It is well known that skin wounds generally heal by scarring, a fibrotic process mediated by the Engrailed-1 (En1) fibroblast lineage.…”
Section: Discussionmentioning
confidence: 99%
“… 110 The degradation rate of PCL is lower than other materials (such as PGA, PLGA, and Poly L-lactic acid (PLLA)) 111 ; therefore, PCL nanofibers provide a long-term mechanical support in defective tissue. To reduce excessive scarring in wound healing, Kim et al 112 fabricated electrospun nanofibrous meshes, composed of haloarchaea-produced biodegradable elastomer poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) as a wound dressing. And the results demonstrated that electrospun nanofibrous PHBV meshes mitigate excessive scar formation by regulating myofibroblast formation, showing their promise for use as wound dressings.…”
Section: The Essential Elements For Skin Bioprintingmentioning
confidence: 99%
“…The utilization of BGs as a dental material began in the mid-1980s, when BGs were successfully used to preserve the alveolar bone of edentulous patients [15]. Furthermore, BGs have been developed into bioactive glass nanoparticles (BGns), which have a high surface area, bioactivity, and antibacterial effect [16,17]. Many researchers have attempted to mix BGns with various materials and have reported improvements in mechanical properties, bioactivity, and mineralization capacities [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%